COMPARISON OF THREE DIFFERENT CONFIGURATION POSTERIOR INSTRUMENTATION OF SYNBONE® BONE MODEL OF ADOLESCENT IDIOPTAHIC SCOLIOSIS LENKE 1: IN VITRO TEST OF BIOMECHANICAL - S. Dohar Tobing; Hendar Nugrahaedi Priambodo (Journal of Global Pharma Technology, 2018)
Introduction. Biomechanical construction test of posterior instrumentation for scoliosis correction is needed to evaluate reliability and instrumentation performance. Latest biomechanical testing have validated bone model as a suitable substitute. Low pedicle screw density can correct without significant complication. This study compared biomechanics of three posterior instrumentations: Bilateral Pedicle Screw (BPS), pedicle screw on proximal end, apex, distal end concave side (PAD), and PAD with sublaminar wire the concave side (PAD+SW).Method. Three groups of vertebral model of Scoliosis Lenke I Synbone® is equipped with configurations of 15 samples posterior instrumentations divided into three groups of BPS, PAD, PAD+SW. Each of the static test is given axial force gradually from 50N, 100N, 150N, and 200N using Tensilon® AMD RTF-1310 from Japan, with dial indicator Mitutoyo, Japan. Total displacement were measured for each groups. Stiffness were also analyzed using load-displacement ratio.Results. BPS as the current gold standard showed minimal displacement, followed by BPS, PAD and PAD+SAW for 50N (p<0.001), 100N (p<0.001), and 200N (p<0.001) force, and was not significant for 150N (p=0.086). There was also significant difference between the stiffness of BPS, PAD and PAD+SW for 50N (p=0.002), 100N (p<0.001), 150N (p<0.001) and 200N (p<0.001)Conclusion. For biomechanical testing with static test, type of posterior instrumentations showed significance relationship with displacement and stiffness. BPS groups were more rigid compared to PAD+SW and PAD. Low density of pedicle screw resulted in the decrease of stiffness and posterior instrumentation sublaminar wire addition significantly added the strength.Keywords: Posterior instrumentation, adolescent idiopathic scoliosis, Lenke I, In Vitro